Características da carcaça e da carne de cordeiras pantaneiras abatidas com diferentes espessuras de gordura subcutânea - Mora, Natália Holtz Alves Pedroso (2015)
The objective of this study was to determine the thickness of subcutaneous fat ideal slaughter; check physiological maturity and the meat characteristics of Pantaneiro lambs slaughtered with different thickness of subcutaneous fat (SFT). A field experiment was conducted using 24 female lambs, with approximately 100 days of age and average initial weight of 16.24 ± 1.78 kg, all of the Pantaneiro genetic group, in a completely randomized design with three treatments (2,00; 3,00 e 4,00 mm SFT) and eight repetitions. For all analyzes was adopted the 0.05 significance level. The females were randomly distributed in individual boxes, with suspended slatted floor. The animals received water ad libitum throughout the experimental period and were fed complete and pelleted feed formulated for a daily gain of 0.30 kg. The ratings by ultrasound between the 12th and 13th ribs, and weighing were performed every 15 days. As lambs reached the predetermined SFT, they were slaughtered the day after the measurements, regardless of weight. Article 1: For allometry in carcass, neck and rib showed isogonic growth in all treatments. However, the shoulder, loin and leg cuts showed heterogonic growth for the treatments 2.00 and 3.00 mm STF. There was a transition to isogonic growth from the treatment 4.00 mm STF. The leg and shoulder cuts in relation to half carcass showed the greatest correlation (0.83). The cuts have different growth rates in the tissue components. It is recommended to slaughter female lambs when they reach 3.00 mm of subcutaneous fat thickness, since the carcass has already reached physiological maturity. Article 2: For the physicochemical characteristics of meat, the pH values for 0 hour (6.58); 24 hour (5.50) and cooking losses (23.99%) did not differ between treatments. As for coloring meat, lambs slaughtered with 2.00 mm and 3.00 mm showed meat with higher luminosity; however animals with 3.00 and 4.00 mm were superior to the intensity of red a* and intensity of yellow b*. Females slaughtered with 4.00 mm of SFT (1.43 kgf) was more soft meat than the 2.00 mm (2.52 kgf). Lambs slaughtered at 4.00 mm were higher (1.47 μm) for sarcomere length. The crude protein (21.15%) and moisture (72.38%) samples of treatment 2.00 mm were superior to 4.00 mm (19.75%, 70.39% respectively). The total lipids (4.84%) in the meat of animals slaughtered at 4.00 mm were higher than 2.00 mm (2.79%). There were no differences for contents of ash with an average 1.87%. The slaughter of animals with 3.00 mm thickness of fat in loin is recommended because it encompassed a greater number of favorable characteristics in relation to the chemical composition of meat, softness and color. Article 3: The SFT did not alter the fatty acid profile of meat from Pantaneiro lambs. For the sensory analysis, the meat from the animals slaughtered with 4.00 mm SFT received the best score for variables overall acceptance and characteristic flavor as compared with the females slaughtered with 2.00 mm SFT. The treatment with 3.00 mm SFT, however, did not differ from the others. For sensory traits odor and juiciness, no effect of SFT was found. It is recommended to slaughter lambs with 3.00 mm thickness of subcutaneous fat on the loin, because covered better number of favorable attributes in sensory analysis.